Water Management of Arabica Coffee Seedlings Cultivated with a Hydroretentive Polymer - Mateus Oliveira Silva; Vanessa Reniele Souza de Arruda; Francisco Raylan Sousa Barbosa; Michel Wakim Mendes Firmino; Adriene Woods Pedrosa; Fernando França da Cunha (Agronomy)
The production of high-quality coffee seedlings is essential to meet the demands of the coffee sector, requiring more efficient and sustainable water management practices. In this context, the use of hydroretentive polymers, particularly biodegradable ones, emerges as a promising alternative to optimize water use, reduce the environmental impact associated with synthetic polymers, and improve the agronomic traits of seedlings. Therefore, this study aimed to evaluate the effects of different irrigation intervals and hydroretentive polymer doses on the water consumption and agronomic characteristics of Coffea arabica L. seedlings. This study was conducted in a protected environment using a randomized block design with split plots and four replicates. The plots consisted of two irrigation intervals (2 and 4 days), and the subplots included four doses of hydroretentive polymer (0%, 0.25%, 0.5%, and 1%), applied in 0.5 dm3 polypropylene bags. Results showed that the 0.5% polymer dose combined with a 2-day irrigation interval resulted in the highest water consumption, while the combination of 0% polymer and a 4-day irrigation interval led to the lowest water consumption. The 0.25% hydroretentive polymer dose with irrigation every 2 days showed the best performance in gas exchange, promoting photosynthesis without causing water saturation. This management also promoted better seedling growth, increasing biomass, height, leaf area, and root volume compared to longer irrigation intervals. The crop coefficients (Kc × Ks) were 0.20, 0.28, and 0.45 during the periods of 0–50, 51–80, and 81–150 days after sowing, respectively. A dose of 0.25% hydroretentive polymer with a 2-day irrigation interval is recommended for the production of Arabica coffee seedlings, contributing to agricultural practices aligned with environmental preservation and productive efficiency.